A UTILIZACAO DAS PRESSOES DESENVOLVIDAS NA DETERMINACAO DA VELOCIDADE DE CONTRACAO MAXIMA. POSSIVEL INFLUENCIA DA CONTRACAO ASSINCRONICA - Tucci, P. J.F. (My University, 1973)
Results of Vmax from a control group of dogs were compared with two other groups, in which the contractile state was previously altered by the administration of propranolol or atropine. When utilizing total pressures, the mean values for Vmax did agree with the pharmacological agents employed. When developed pressures were used, the mean values for each group did not agree with the expected inotropic changes. The fact that the pressure velocity ratios with developed pressures showed a peculiar behavior in the beginning of isovolumetric systole suggests that the asynchronous contraction of the left ventricle during the period may invalidate the method of developed pressures for Vmax determination.
The use of developed pressures in determining maximal velocity of contraction; possible influence of asynchronous contraction